Effectiveness of Motivational Interviewing to Facilitate Behavioral Change among Community Health Workers at Kaiwara - An interventional study - Shenoy, Sneha; Sagarkar, Anitha R.; Krishnappa, Pushpanjali; Tasneem, Anam (Journal of interdisciplinary dentistry, 2024)
Aims: To assess effectiveness of MI to facilitate behavioral change among community health workers at Kaiwara. Settings and Design: Randomized Controlled Trial was conducted among health workers of Primary Health Centre area with 40 subjects in two groups. Materials and Methods: A validated questionnaire was used to collect data regarding their demographics and for pre and post assessment of study participants. Principal Investigator (PI), as trained MI Interventionist conducted the MI sessions among study group (MI Group) and delivered conventional Health Education (HE) among control group (HE group). Statistical Analysis Used: Intervention outcome at first, second and third month were Repeated Measure ANOVA, Paired t test and Unpaired t test. Results: The present study showed there was improvement in the mean score in MI and HE groups from baseline to follow up which was statistically significant (P<0.001). At baseline there was no statistically significant difference in mean scores between MI and HE groups (P>0.05). Conclusions: The present study showed MI to be an effective approach to facilitate behavioral change among health workers to incorporate oral health information in their general health promoting activities as compared to conventional HE method.